P537 Adalimumab: Relevance of drug trough levels and antibodies assessment in the prognosis of Crohn's disease. (16th January 2018) - Perdigoto, D; Macedo, C; Portela, F; Lopes, S; Ferreira, M; Mendes, S; Ferreira, M; Tomé, L
Abstract: Background: Monitoring of infliximab therapy in inflammatory bowel disease (IBD) is well established. As for adalimumab, there is less consolidated data. This study aimed to evaluate the usefulness of adalimumab trough levels (ATL) and serum anti-adalimumab antibodies (AAA) in the control of Crohn's disease (CD). Methods: This is a retrospective study assessing patients with CD treated with adalimumab followed in a tertiary hospital. Remission was defined as the absence of symptoms and C-reactive protein (CRP) value ≤ 0.5 mg/dl. All patients were on treatment for at least eight weeks. Drug quantification: ATL was always measured immediately before the next drug administration (the patients with ATL between two drug administrations or after taking the drug were exclude). Statistical significance was considered when p <0.05. Results: Fifty patients were included. The majority were female (54%) with a mean age of 35.8 ± 12.8 years. Mean ATL of 6.94 ± 4.30 μg/ml. Most patients (82%) did not have AAA. The presence of AAA did not influence ATL ( p = 0.104). ATL were statistically higher in patients submitted to immunomodulatory (combined) therapy: 8.10 ± 3.63 vs. 5.69 ± 4.68 μg/ml ( p = 0.047). ATL statistically correlated with the presence of remission–AUC = 0.714 ( p = 0.038), with a cut-off of 7.60 μg/ml as an indicator of remission at any time point (sensitivity 51.3% and specificity 100%). The presence of AAA correlated with the absence of immunomodulatory therapy ( p = 0.009). Remission correlated only with ATL ( p = 0.045). Conclusions: Only the ATL statistically correlated with remission. Combined therapy had a protective effect by reducing antibody formation and optimising drug levels. The generation of antibodies seems less frequent when compared with other biological drugs. Additionally, when antibodies exist, they are not always deleterious. The 7.60 μg/ml threshold as an indicator of remission is among the values reported in the literature (between 5 and 8 μg/ml). However, the ability to predict remission with this value is limited.